Willy Brandt : Life of a Statesman$dMiard-Delacroix, Helene - Miard-Delacroix, Helene (I.B.Tauris, 2016)
Author bio -- Endorsements -- Title page -- Copyright page -- Contents -- List of Illustrations -- Abbreviations -- Preface -- Prologue -- 1 Between Attachment and Emigration -- 2 In Berlin, at the Heart of the Cold War -- 3 From Party Chairman to Foreign Minister -- 4 The Chancellor of Ostpolitik -- 5 'Dare More Democracy' or a Difficult Promise -- 6 After Power -- 7 The End of the Story? -- Notes -- Bibliography -- Plates